Identification of KLHL40 mutations by targeted next‐generation sequencing facilitated a prenatal diagnosis in a family with three consecutive affected fetuses with fetal akinesia deformation sequence. (18th November 2016) - Chen, Tai‐Heng; Tian, Xia; Kuo, Pao‐Lin; Pan, Hui‐Ping; Wong, Lee‐Jun C.; Jong, Yuh‐Jyh
Abstract: Background: Fetal akinesia deformation sequence (FADS) refers to a broad spectrum of disorder with the absent fetal movement as the unifying feature. The etiology of FADS is heterogeneous, and the majority remains unknown. Prenatal diagnosis of FADS because of neuromuscular origin has relied on clinical features and fetal muscle pathology, which can be unrevealing. The recent advance of next‐generation sequencing (NGS) can provide definitive molecular diagnosis effectively. Methods and Results: An 18‐week‐old fetus presented with akinesia and multiple contractures of joints. The mother had two previously aborted similarly affected fetuses. Clinical diagnosis of FADS was made. Molecular diagnosis using cord blood by NGS of genes related to neuromuscular diseases revealed two compound heterozygous mutations; c.602G > A(p.W201*) and c.1516A > C(p.T506P), in the Kelch‐like 40 (KLHL40) gene. Based on this information, prenatal diagnosis was performed on the CVS of the subsequent pregnancy that resulted in an unaffected female baby, heterozygous for the c.1516A > C(p.T506P) mutation. Conclusion: Identification of KLHL40 mutations in one of the aborted fetuses provided a confirmative diagnosis of FADS, facilitating the prenatal diagnosis of the subsequent pregnancy. This report underscores the importance of target NGS in providing FADS families with an affordable, precise molecular diagnosis for genetic counseling and options of prenatal diagnosis. © 2016 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? FADS is clinically and genetically heterogeneous, difficult to diagnose. A devastating condition, yet, a quick definitive prenatal diagnosis is not available. What does this study adds? We have utilized a high throughput next-generation sequencing (NGS) approach to capture and sequence all target genes known to cause FADS. The targeted gene capture followed by NGS provides an alternative clinical utility that is readily available for precise molecular and prenatal diagnosis of FADS.